La violencia de género y su relación con los rasgos de personalidad dependiente de mujeres entre 18 a 55 años de edad que acuden a la Fiscalía Provincial de Loja. - Piedra Jiménez, Katerinn Sofía (2017)
GENDER VIOLENCE is a social phenomenon which it has been accepted as part of our culture an in many cases it has been because of a lack of education and poor self steam. The present research includes the study of many cases of alleged victims of gender violence, all these cases has been registered in the Unit of Attention and Integral Assessment (UAPI), in the office of the Provincial Prosecutor of Loja and its relationship with DEPENDANT PERSONALITY CHARACTERS. During the process it has been found that many of the victims had created a dependent personality link with the abuser, where the victim, it has approved this life style of aggression not only verbal abuse but physical too. A cross-sectional, descriptive study with a quantitative-qualitative approach was carried out with 71 people, aged 18-55 years, using the Multiaxial Million Inventory (MCMI-II). At the end of the investigation, the results proved that 100% of the women evaluated had suffered gender violence, and the personality traits that influence their permissiveness are: 27% dependent and 18% compulsive. To sum up the results, the present work culminates in the elaboration of a therapeutic plan aimed at preventing and eliminating these repetitive behaviors of violence, and the negative repercussions on their personal, family and social life. keywords: violence, women, victims, personality, dependant